Clinical Holistic Medicine: The Patient with Multiple Diseases - Søren Ventegodt; Joav Merrick (The Scientific World Journal)
In clinical practice, patients can present with many different diseases, often both somatic and mental. Holistic medicine will try to see the diseases as a whole, as symptoms of a more fundamental imbalance in the state of being. The holistic physician must help the patient to recover existence and a good relationship with self. According to the life mission theory, theory of character, and holistic process theory of healing, recovering the purpose of life (the life mission) is essential for the patient to regain life, love, and trust in order to find happiness and realize the true purpose of life. We illustrate the power of the holistic medical approach with a case study of an invalidated female artist, aged 42 years, who suffered from multiple severe health problems, many of which had been chronic for years. She had a combination of neurological disturbances (tinnitus, migraine, minor hallucinations), immunological disturbances (recurrent herpes simplex, phlegm in the throat, fungal infection in the crotch), hormonal disturbances (14 days of menstruation in each cycle), muscle disturbances (neck tensions), mental disturbances (tendency to cry, inferiority feeling, mild depression, desolation, anxiety), abdominal complaints, hemorrhoids, and more. The treatment was a combined strategy of improving the general quality of life, recovering her human character and purpose of life (“renewing the patients life energy”, “balancing her global information system”), and processing the local blockages, thus healing most of her many different diseases in a treatment using 30 h of intense holistic therapy over a period of 18 months.